2019
DOI: 10.1002/er.4522
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory investigation on the use of thermally enhanced phase change material to improve the performance of borehole heat exchangers for ground source heat pumps

Abstract: Summary Ground source heat pumps have high efficiency and high capital cost primarily due to borehole drillings. This research investigates the inclusion of high‐conductivity phase change material (PCM) in the borehole heat exchanger of a ground source heat pump to reduce the borehole length required and improve its coefficient of performance (COP). In the laboratory model, the borehole heat exchanger was represented by a cylindrical electrical heater having a total power of 9.216 W, operating for 1 hour while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Changing the physical state is crucial for the proper implementation of these materials, which is why attention should be focused on the phase change temperature (PCT). It is recommended to use several PCM materials with different PCT to cover a greater operating temperature range, i.e., heating and cooling periods [140]. The term PCM corresponds to a wide variety of materials categorized into organic, inorganic, solid-solid, and hygroscopic materials.…”
Section: Backfill and Grouting Materialsmentioning
confidence: 99%
“…Changing the physical state is crucial for the proper implementation of these materials, which is why attention should be focused on the phase change temperature (PCT). It is recommended to use several PCM materials with different PCT to cover a greater operating temperature range, i.e., heating and cooling periods [140]. The term PCM corresponds to a wide variety of materials categorized into organic, inorganic, solid-solid, and hygroscopic materials.…”
Section: Backfill and Grouting Materialsmentioning
confidence: 99%
“…Bottarell et al [8,9] adopted the numerical simulation to study the effect of adding PCM to backfill materials on the heat transfer performance of horizontal buried pipe heat exchanger, and the results showed that PCM could slow down the soil temperature rise and improve the heat pump performance. Lyne et al [10] discussed the effects of soil, PCM, and graphite PCM backfill materials with high conductivity on the temperature of heat exchange boreholes, and the results showed that PCM could reduce the soil temperature fluctuation. Yang et al [11][12][13] tested and simulated the energy storage and heat transfer characteristics of PCM-backfilled buried heat exchangers, and the results showed that in both summer and winter, PCM backfilling could improve the energy storage performance, reduce the variation range of soil temperature outside the boreholes, enhance the recovery rate of soil temperature, and decrease the heat effect radius of borehole.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a substantial increase in heating COP of 4.6 for GSHP system against 3.1 for the VRF system, while the cooling COP was enhanced to 3.3 from 2.1. A research has been conducted to investigate the inclusion of high conductivity phase change material (PCM) in the borehole heat exchanger of a GSHP to reduce the borehole length required and improve its COP 20 . Results from their experiments revealed that the maximum COP values of a GHSP calculated assuming an ideal reversed Carnot cycle for cooling mode showed an increase of approximately 81% with PCM and by 112% with graphite enhanced PCM.…”
Section: Introductionmentioning
confidence: 99%